Offshore threats: Liquefied natural gas, terrorism, and environmental debate in Connecticut - Harrison, Blake (Annals of The Association of American Geographers, 2008)
Broadwater Energy is one of a number of recent proposals to construct a liquefied natural gas facility along the East Coast of the United States. The proposal calls for the construction of an import and regasification terminal in Long Island Sound, roughly halfway between the states of New York and Connecticut. First made public in 2004 by its sponsors, TransCanada and Shell, the Broadwater proposal has inspired opposition from a range of interest groups. An examination of the Broadwater debate with a focus on arguments made by Connecticut residents in the months leading up to the release in late 2006 of the proposal's Draft Environmental Impact Statement reveals explicit and implicit points of overlap between concerns about the facility's environmental impacts and concerns about its status as a potential terrorist target. Discussions about terrorism deployed in the Broadwater debate have initiated and informed a politics of scale through which themes common to environmental debates have been transformed. This transformation, in turn, highlights the discursive and material influence of terrorism in contemporary U.S. society. Concerns about terrorist attacks have been deployed by activists to enhance the strength of an otherwise environmental debate and, in the process, those concerns have developed the potential to shape land use policy in Long Island Sound. Key Words: environmentalism, liquefied natural gas, Long Island Sound, scale, terrorism.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-913-849-043-885 tex.unique-id: [object Object]
Keywords: Connecticut; Environmentalism; Liquefied natural gas; Long Island Sound; North America; Scale; Terrorism; United States; container terminal; dept.egm; environmental impact; environmental policy; environmentalism; land use planning; liquefied natural gas; offshore engineering; terrorism